Effects of supine floating on cardiac autonomic nervous system activity after treadmill exercise in water - Kazuki, N.; Kazutoshi, S.; Daisuke, N.; Takeshi, O.; Eri, O.; Kumikol, O.; Sho, O. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to determine the effects ofsupine floating on rectal temperature and cardiac autonomic nervous system activity after treadmill exercise in the water. Six healthy males volunteered for this study. Subjects were placed in a supine position for 30 minutes in both a water condition (W-condition) and control condition (C-condition) after treadmill exercise in the water. And subjects were measured for recovery while sitting for 15 minutes. During supine floating after treadmill exercise in the water, log HF was significantly increased (p< 0.05) under theW-condition, as compared to the C-condition, during the recovery process. These data suggest that supine floating after treadmill exercise in the water could increase cardiac parasympathetic nervous system activity. Also, the increase in cardiac parasympathetic nervous system activity continues for recovery while sitting after supine floating.